Cancer-associated fibroblasts in clear cell renal cell carcinoma: functional heterogeneity, tumor microenvironment crosstalk, and therapeutic opportunities - Wang, Man; Zhao, Yuanzhuo; Xu, Kangchun; Liu, Chao; Zhong, Hui; Wu, You; Zhang, Ke; Wei, Shanzhai (Frontiers in Immunology, 2025)
Clear cell renal cell carcinoma (ccRCC) progression heavily relies on the immunosuppressive tumor microenvironment (TME). In the ccRCC TME, the cancer-associated fibroblasts (CAFs) drive a self-perpetuating cycle of immune evasion and therapeutic resistance through diverse interactions between cells and molecules. Furthermore, heterogeneous CAFs facilitate tumor growth through metabolic reprogramming and modulate immune suppression by driving the M2 polarization of tumor-associated macrophages (TAMs) and the expansion of regulatory T cells (Tregs), which promote a multilayered immunosuppressive network. In addition, CAFs reshape the mechanical properties of extracellular matrix (ECM), hinder the infiltration of cytotoxic T lymphocytes (CTLs) and further exacerbate immune escape. Moreover, CAF-derived exosomes can confer resistance to chemoradiation therapy. Interleukin-6 (IL-6) secreted by CAFs synergizes with vascular endothelial growth factor (VEGF) to facilitate adaptive resistance to targeted therapy. Emerging therapeutic strategies—including fibroblast activation protein (FAP)-targeted CAR-T cells and transforming growth factor-β (TGF-β) inhibitors—can partially reverse this immunosuppressive property. Combination therapies employing immune checkpoint inhibitors and VEGF antagonists exhibit promising synergistic effects, although the clinical translation remains hampered by CAF heterogeneity, dual functional roles, and the lack of specific biomarkers. Future studies should integrate single-cell sequencing and spatial multi-omics techniques to comprehensively analyze the spatio-temporal dynamic heterogeneity of CAF subpopulations and develop precision treatment strategies based on molecular subtyping, aiming to break the vicious cycle of “CAF-TME-resistance” in ccRCC.